2000
DOI: 10.1159/000012139
|View full text |Cite
|
Sign up to set email alerts
|

bcl-2 Expression in Cholangiocellular Carcinoma Is Inversely Correlated with Biologically Aggressive Phenotypes

Abstract: bcl-2 is known to play a crucial role in modulating carcinoma progression as well as in inhibiting apoptosis. However, its expression and clinical significance for cholangiocellular carcinoma (CCC) remains unclear. In the present study, we immunohistochemically investigated bcl-2 expression in 41 CCC. Thirteen cases (31.7%) were classified as bcl-2 positive, because more than 10% of the carcinoma cells expressed bcl-2. The expression of bcl-2 was inversely related to lymph node metastasis, vascular invasion, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Previous studies have examined the potential role of known genes involved in human carcinogenesis to elucidate the molecular pathways involved in cholangiocellular carcinoma, for example, members of the type Ⅰ family of growth factor receptors (EGF-R, c-erbB-2) [14][15][16] , (proto-) oncogenes (c-met, c-Ki-ras, Cyclin D) [17][18][19] , dysregulated tumor-suppressor genes (p53, pRB, p16INK4a, p21WAF1) [20,21] , and apoptosis-related genes (bcl2, FAS-L, BAX) [22,23] . Other studies have shown microsatellite instability and loss of heterogeneity (LOH) as contributing factors in the development of CCC [24,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the potential role of known genes involved in human carcinogenesis to elucidate the molecular pathways involved in cholangiocellular carcinoma, for example, members of the type Ⅰ family of growth factor receptors (EGF-R, c-erbB-2) [14][15][16] , (proto-) oncogenes (c-met, c-Ki-ras, Cyclin D) [17][18][19] , dysregulated tumor-suppressor genes (p53, pRB, p16INK4a, p21WAF1) [20,21] , and apoptosis-related genes (bcl2, FAS-L, BAX) [22,23] . Other studies have shown microsatellite instability and loss of heterogeneity (LOH) as contributing factors in the development of CCC [24,25] .…”
Section: Discussionmentioning
confidence: 99%
“…56 Other alterations that seem to occur early in cholangiocarcinogenesis include overexpression of the receptor tyrosine kinases (RTKs) ErbB-2 and Met 2,27,57-59 and the upregulation of COX-2. 2,26,27 Moreover, strong expression of ErbB-2, 2,27,57 Met, 27,58,59 COX-2, 2,27 Bcl-2, 60 and Fas ligand 61 have been detected more frequently in well-differentiated cholangiocarcinomas compared with moderate to poorly differentiated tumors, whereas downregulation of ␤-catenin and E-cadherin, 62,63 overexpression of aspartyl (asparaginyl) ␤-hydroxylase, 64 and decreased expression of such factors as Fas receptor 61 and p57 kip2 65 correlated with higher histological grades of tumor. No correlation was found between p27 kip1 expression and tumor grade, but low p27 kip1 expression was shown to be an independent predictor of survival for patients with either peripheral or hilar cholangiocarcinoma.…”
Section: Sirica Hepatology January 2005mentioning
confidence: 99%
“…Furthermore, these expression patterns may explain the controversial Bcl-2 data generated by previous studies. Most studies investigating Bcl-2 expression in ChCs have reported varying degrees of Bcl-2 protein expression [8, 16, 18, 23, 24]. A study by Charlotte et al [8] showed that the Bcl-2 protein is expressed by small bile duct epithelia in normal livers but not by hepatocytes or cells of the large duct.…”
Section: Discussionmentioning
confidence: 99%